The Crystal Palace Debates: The Emergence of a Working-Class Leisure Public in Mid-Victorian Britain - Morris, Josh M. (Tufts Archival Research Center, 2023)
This thesis examines the story of the Crystal Palace, focusing on the period from the end of the Great Exhibition of 1851 to its reopening on Sydenham Hill in 1854. The fierce public debates surrounding the Palace illuminate the emergence of a working-class leisure public and its connection to the development of commercial popular recreation. However, despite the grand vision of the Palace as a beacon of progress through rational recreation, its fate was shaped by the limitations of progress. Parliament failed to respond to the popular will, siding with the aristocratic Kensington neighborhoods to remove the Palace from Hyde Park and yielding to Sabbatarian agitators who opposed Sunday opening. Furthermore, commercial realities revealed cracks in the New Palace’s progressive dreams even in its earliest days. As a microcosm of a moment of rapid social change, the Crystal Palace debates exemplify the tensions between progress and conservatism in Mid-Victorian society.; Thesis (B.A.)--Tufts University, 2023.; Submitted to the Dept. of History.